(untitled) (Asian Journal of Medical and Biological Research, 2018)
This study was conducted to know prevalence of gestational diabetes and associated factors. A cross sectional data was collected from the pregnant mothers from a hospital of Barisal city, Bangladesh. It was revealed that 5% of the interviewed mothers suffer from diabetes. Among 100 participants, 58% were in 20-30 years age group and 68% patients married within 21-25 years old. Near about half (51%) of mothers had more than 60 Kg body weight. Maximum (48%) patients passed their secondary education and 78% were jobless. More than half (56%) of the patient’s family monthly earned 10000-20000 BD Tk. Among the mothers, 15% had the family history of diabetes. Correlation matrix revealed that, body weight, and blood pressure were positively associated with sugar level. Gestational age (P=0.04261) and diastolic blood pressure (P=0.018764) were significantly associated with the RBS of pregnant mothers. More study should be conducted to explore the accurate prevalence and practices of diabetic patients in the study area. Asian J. Med. Biol. Res. September 2018, 4(3): 274-278